Testing the Weak Form Efficiency with Respect to Sectoral Indices of National Stock Exchange Limited, India - Selvam, Murugesan; Ramkumar, Ramachandran Rajesh; Lingaraja, Kasilingam (Indian Journal of Research in Capital Markets, 2016)
The capital market is a vital institution as it facilitates economic development of a country. Investors need to know the efficiency of the stock market to invest their hard-earned money in a profitable way, while the policy makers need the latest information about different indices to devise appropriate policies. Thus, the efficiency of sectoral indices could also help the government to identify efficient sectors and to channel available resources for the growth of such sectors. This paper proposes to investigate the capital market efficiency in NSE (National Stock Exchange) sectoral indices by using daily share price returns. The aim of this study was to examine the weak form efficiency of the selected indices listed in NSE. The study found from the results of sectoral indices that NSE could not be considered under weak form efficiency during the study period.